Предельные давления для формообразования при холодной вытяжке листового материала - Автономова, Людмила Владимировна; Дергун, С. М.; Лавинский, Владимир Иванович; Панасенко, С. И. (НТУ "ХПИ", 2007)
The method of estimation of maximum pressures for creation of spherical extraction of the given depth in a lamina under action of the even pressure is given. Quantitative information is resulted for plates from basket motor-car steels.
Keywords: автомобилестроение; пластинчато-оболочечные элементы; ребра жесткости; пластическая обработка; сферическая вытяжка; теория пластического течения